Obstetric Outcomes of Adolescent Pregnancies in Turkey - Canbaz, S; Sunter, AT; Cetinoglu, CE; Peksen, Y (Springer, 2005)
Pregnancy in adolescence has been and continues to be a problem in public health. The purpose of this study was to investigate obstetric outcomes of adolescent pregnancies in Samsun, Turkey. A cross-sectional study was conducted between January 1 and December 31, 2004, at 3 hospitals in Samsun, Turkey. Of the 10,100 women who gave birth during this period, 357 (3.5%) were 18 years of age or younger; these patients were included in the study. Participants with a history of any chronic disease were excluded. Data were provided as median values (min-max) and percentages. In this study, the rate of birth for females 18 years or younger was found to be 35 per 1000. The median age of participants was 18 (14-18) years. The prevalence of cesarean section was calculated at 55.7%. Prevalences of low-birthweight infants, preterm delivery, and eclampsia/preeclampsia were recorded as 44 (12.3%), 34 (9.5%), and 30 (8.4%) cases, respectively. Although the stillbirth rate was determined to be 1.7%, no congenital deformity was noted in infants, and none of the mothers died. The cephalopelvic disproportion rate was 5.9%, and only 2 adolescents experienced abruptio placentae. To reduce the occurrence of adolescent childbearing, pregnancy intentions must be assessed in multiple ways. Information/education may provide benefit to those female adolescents with inconsistent pregnancy intentions.
Keywords: Pregnancy; Adolescence; Obstetric Outcome; Turkey